1996
DOI: 10.1099/13500872-142-8-2105
|View full text |Cite
|
Sign up to set email alerts
|

16S-23S rDNA intergenic sequences indicate that Leuconostoc oenos is phylogenetically homogeneous

Abstract: The study of the intra-specif ic phylogenetic structure of Leuconostoc oenos is essential to understand the participation of several strains in malo-lactic fermentation (MLF). RFLP of the PCR-amplified 165-23s rDNA intergenic spacer region (ISR) was performed in Leuc. oenos and other related species. The RFLP patterns with seven endonucleases were identical for the 37 Leuc. oenos strains, but differed from those obtained for all other species tested. This method could provide an invaluable insight for molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
67
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 52 publications
7
67
1
1
Order By: Relevance
“…The extensive degree of conservation of the order of loci presented here supports the previously suggested homogeneous nature of O. oeni (Morse et al, 1996 ;Zavaleta et al, 1996Zavaleta et al, , 1997. As suggested by St.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The extensive degree of conservation of the order of loci presented here supports the previously suggested homogeneous nature of O. oeni (Morse et al, 1996 ;Zavaleta et al, 1996Zavaleta et al, , 1997. As suggested by St.…”
Section: Discussionsupporting
confidence: 77%
“…O. oeni has a restricted ecological niche (wine and related habitats), a peculiar acidophilic nature and viability at high ethanol levels (Garvie, 1986) and, although its dissimilarity to other leuconostocs is fully accepted, there is some controversy regarding both the evolution rate of the species (Martı! nez-Murcia et al, 1993 ;Morse et al, 1996) and its diversity (Dicks et al, 1990 ;Zavaleta et al, 1996). Based on metabolic\physiological criteria, splitting of O. oeni into two species was once proposed (Peynaud & Domercq, 1968), but the levels of DNA-DNA homology (73-110 % ; Dicks et al, 1990) are in agreement with the genomic concept of bacterial species.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…This contributes to a high mutation rate, an excess of recombination, and a rapid genetic evolution and is characterized by a lack of certain genes and highly divergent sequences (19). However, several studies based on the sequencing of the 16S, 23S, and 16S-to-23S intergenic spacer region (ISR) sequences suggested that the species O. oeni is genetically homogenous (14,20,21,26). This was reinforced by the levels of DNA-DNA homology and by the similarities of genetic maps observed for various strains (8,27).…”
mentioning
confidence: 99%
“…Methods for typing O. oeni strains include the study of patterns of total soluble cell proteins (11,13), ribotyping (58), 16S and 23S rRNA spacer region analysis (26,64), randomly amplified polymorphic DNA (RAPD)-PCR (3,17,43,62), pulsed-field gel electrophoresis (PFGE) (22,24,27,51,65), differential display PCR (25), and amplified fragment length polymorphism (AFLP) analysis (6). Being easy to use, RAPD and multiplex RAPD assays have been employed to study O. oeni population dynamics in wine and to check which strains really are responsible for MLF (43,44,54,62).…”
mentioning
confidence: 99%